Legal Protection of Land Rights Certificate Holders in Certificate Blocking Event by Land Office - Edi Mulyanto; Siti Ummu Adillah (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The certificate is a certificate of proof of rights that applies as a strong means of proof regarding physical data and juridical data, and this evidence is not the only evidence, only strong evidence. This research uses sociological juridical. Sociological juridical research identifies and conceptualizes law as a real and functional social institution in a real life system. This study comes in: 1) Blocking Defects in Article 1 point (1) of the Regulation of the Minister of ATR/Head of BPN Number 13 of 2017 about the procedure for blocking and confiscation is an administrative action of the Head of the Land Office or an appointed official to determine the status quo (freezing) on temporary land rights against changes to land law. 2) The state should protect the holder of the Land Rights Certificate because of the good faith of the holder and the state's decision to issue a certificate as proof of land rights which the state should not cancel without compensation. 3) Blocking that is not in accordance with Permen ATR/Ka.BPN 13 of 2017 about the procedure for blocking and confiscation does not only result in legal certainty not being realized, but also causes losses for the owner of the blocked certificate, both material and immaterial losses. Blocking cases has the potential to cause financial losses to the owner of the blocked certificate. Due to the block, the owner cannot access his land certificate. 4) Obstacles to land rights holders in the registration of the block because the land rights are disputed and confiscated by the Court or a dispute outside the court, the Land Rights are confiscated by PUPN/KPKNL in connection with the settlement of state receivables, so the parties are requested by the Head of the Land Office for blocking. The legal consequences for the owner of the certificate for blocking the Certificate of Land Rights at the Land Office are that the land is temporarily unable to take legal action and also the Land Office has the authority to refuse the registration of the Transfer and Transfer of Names to the Land Rights.